Fundamentals and Applications of Comparative Innovative Trend Analysis - Yavuz Selim Güçlü (Doğal Afetler ve Çevre Dergisi)
Nowadays, innovative trend analysis methodology proposed by Şen became to be employed for trend identification studies, since it presents visual inspection of trends, which is the subject of this study. On basis of this methodology, an alternative one is proposed as comparative innovative trend analysis approach. It helps to compare different data sets interrelated with each other such as temperature, sunshine duration, and solar radiation on the same graph but it is provided that the data must be dimensionless. Hence, comparative results represent four important information, which are visualizations of three data sets separately and comparison of their trend conditions. This study comprises daily total solar radiation, daily total sunshine duration, and daily mean temperature records obtained by Turkish State Meteorological Service in some meteorological stations namely Adana, Antakya, Gaziantep and Şanlıurfa in Turkey. In addition, after the visualizations of comparative innovative trend analysis results for each station, classical innovative trend analysis is implemented to show the superiority of the new method.